Risk aversion and other factors determine income redistribution preferences - Manja Gärtner; Johanna Mollerstrom (DIW Weekly Report, 2018)
The amount of redistribution people favor depends on socioeconomic factors and their views on fairness. This study, based on a representative survey conducted in Sweden, confirms earlier results: Higher incomes are correlated with wanting less redistribution, women are more in favor of redistribution than men on average, and older people favor it more than younger people. People's views on fairness and altruism also play a role. The study also shows for the first time that individual differences in risk aversion correlate with redistributive preferences. People who shy away from risk tend to wish for more redistribution than people who are more prone to taking risks. The results help us understand which policies are supported by which segments of the population.
Keywords: C83; C91; C93; D63; D81; H23; 330; redistribution; inequality; survey; risk aversion